The interesting and complex tribe Oxycoleini (Coleoptera, Cerambycidae): a new genus, new species, and taxonomic notes - de L. Nascimento, Francisco Eriberto; Santos-Silva, Antonio (Zootaxa, 2021)
The inclusion of Tethlimmena Bates, 1872 in Oxycoleini is reinforced, with the consequent exclusion of Eroschemini Lacordaire, 1868 from the American fauna. Oxycoleus obscurus Júlio, 1997 is transferred to Tethlimmena. Wappesia gen. nov. is described to include Oxycoleus cyaneus Martins & Galileo, 2005, Tethlimmena gahani Gounelle, 1911 (currently, in Oxycoleus), and Tethlimmena gahani tristis Melzer, 1933 (currently, in Oxycoleus as O. tristis). A key to genera of Oxycoleini is provided. Two new species of Oxycoleus are described: O mirabilis, from Mexico (Chiapas) and Guatemala (Baja Verapaz); and O. similis, from Costa Rica (Guanacaste) and Panama (Chiriquí). The male of Oxycoleus flavipes Martins & Galileo, 2006 is described for the first time. Notes on O. laetus Júlio, 1997 are provided.